Integrasi Pendidikan Agama Islam untuk Kompetisi Global: Rekonstruksi Epistemologi, Model Kurikulum, dan Implementasi Profil Pelajar Rahmatan Lil Alamin - Muhammad Nurul Maulida; Sari Hernawati; Nanang Nurcholis (STKIP Subang, 2025)
Amidst the massive globalization and disruption of the Industrial Revolution 4.0 era, Islamic Religious Education (PAI) faces existential challenges not only to preserve religious traditions but also to produce globally competitive human resources. This study aims to formulate a comprehensive PAI integration model, from the epistemological foundation to the practical implementation of the curriculum, in order to shape students who are faithful, have noble character, and master 21st-century competencies. Using library research methods with content analysis of authoritative literature and the latest policies, this study found that the paradigm of the dichotomy of knowledge must be replaced by a paradigm of integration-interconnection. The results show that the